2023
DOI: 10.1007/s13300-023-01384-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Obesity and the 5-Year Prevalence of Morbidity and Mortality Among Adults with Type 2 Diabetes

Abstract: Introduction: This retrospective claims database study examined the prevalence of mortality and morbidity among adults with type 2 diabetes (T2D) and obesity. Methods: The study used deidentified data from 2007 to 2021 from the OptumÒ Market Clarity Dataset. A cohort of adults with T2D and obesity were identified, and age-and sex-adjusted prevalence rates were calculated for mortality, a composite cardiovascular outcome (CCO), a composite microvascular outcome (CMO), and other complications. Results were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Both models performed better in non-obese versus obese patients, and in patients who did not have T2D versus those who did. This is likely a result of obese patients and those with T2D having greater variability in EQ-5D-5L values because of the range of complications that frequently exist in individuals with these conditions [ 40 , 41 ], and the coexistence of obesity and T2D in many patients [ 42 ]. We observed that the two best models performed less well at predicting lower versus upper values of EQ-5D-5L.…”
Section: Discussionmentioning
confidence: 99%
“…Both models performed better in non-obese versus obese patients, and in patients who did not have T2D versus those who did. This is likely a result of obese patients and those with T2D having greater variability in EQ-5D-5L values because of the range of complications that frequently exist in individuals with these conditions [ 40 , 41 ], and the coexistence of obesity and T2D in many patients [ 42 ]. We observed that the two best models performed less well at predicting lower versus upper values of EQ-5D-5L.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an estimated 41 million children under the age of five are overweight or obese. It was reported that obesity is a major risk factor for premature mortality [62,63]. In addition, obesity is associated with a higher risk of developing several chronic conditions that can lead to premature death, such as cardiovascular disease, type II diabetes, and some cancers [64,65].…”
Section: Binge Eating Disorder (Bed)mentioning
confidence: 99%
“…Overweight and obesity are associated with metabolic syndrome [ 2 ] and represent major risk factors for the development of type 2 diabetes mellitus (T2DM) [ 1 – 3 ]. The prevalence of T2DM increases linearly with body mass index (BMI) [ 4 7 ], and around 80–90% of diabetic patients are overweight or obese [ 8 ], presenting a greater risk for serious health complications and mortality [ 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral lifestyle interventions often involve a combination of dietary, physical activity, and behavioral components, which involve strategies to promote changes in diet and physical activity [ 7 , 15 17 ]. Although these interventions have a positive impact on physical health and quality of life [ 9 , 15 , 18 , 19 ], evidence about their efficacy in terms of weight loss is still controversial [ 10 , 19 24 ] and results are difficult to maintain in the long term [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%